Conserved Transcriptional Unit Organization of the Cag Pathogenicity Island among Helicobacter pylori Strains - Ta, Linda H.; Hansen, Lori M.; Sause, William E.; Shiva, Olga; Millstein, Aram; Ottemann, Karen M.; Castillo, Andrea R.; Solnick, Jay V. (Frontiers in Cellular and Infection Microbiology, 2012)
The Helicobacter pylori cag pathogenicity island (cag PAI) encodes a Type IV secretion system that is more commonly found in strains isolated from patients with gastroduodenal disease than from those with asymptomatic gastritis. Genome-wide organization of the transcriptional units in H. pylori strain 26695 was recently established using RNA sequence analysis (Nature (2010) vol. 464:250). Here we used quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) of open reading frames and intergenic regions to identify putative cag PAI operons in H. pylori, which were analyzed further by transcript profiling after deletion of selected promoter regions. Additionally, we used a promoter-trap system to identify functional cag PAI promoters. The results demonstrated that expression of genes on the H. pylori cag PAI varies by nearly five orders of magnitude and that the cag PAI genes are organized into transcriptional units that are conserved among several H. pylori strains, including, 26695, J99, G27 and J166. We found evidence for twenty transcripts within the cag PAI, many of which likely overlap. Our data suggests that there are at least eleven operons: cag1-4, cag3-4 cag10-9, cag8-7, cag6-5, cag11-12, cag16-17, cag19-18, cag21-20, cag23-22 and cag25-24, as well as five monocistronic genes (cag4, cag13, cag14, cag15, cag26). Additionally, the location of four of our functionally identified promoters suggest they are directing expression of, in one case, a truncated version of cag26 and in the other three, transcripts that are antisense to cag7, cag17 and cag23. Taken together, our results suggest that the cag PAI transcriptional profile is generally conserved among H. pylori strains, 26695, J99, G27 and J166, and is likely complex.